159 Acute coronary syndrome in patient with giant cell arteritis: a fascinating case. (8th December 2021) - Cumitini, Luca; Giubertoni, Ailia; Rossi, Lidia; Solli, Martina; Bellan, Mattia; Patti, Giuseppe
Abstract: Aims: The diagnosis of acute coronary syndrome with persistent ST segment elevation, although apparently simple to detect by electrocardiographic abnormalities, can sometimes be insidious due to a difficult differential diagnosis with aortic dissection. Performing a coronary angiography in case of aortic dissection can be potentially life-threatening so, when suspected, this diagnosis needs to be rule out. Furthermore, coronary vasculitis is a rare but devastating complication of giant cell arteritis. Methods and results: We describe a case of 62-year-old man hospitalized for acute coronary syndrome with persistent ST segment elevation involving the inferior wall. Ha was a heavy smoker with familiar history of cardiovascular disease and recent suspicion of Horton arteritis with aortic involvement under investigation, no previous cardiological events. Presenting symptoms are chest pain, sweating, bradycardia, and hypotension. In the emergency department, due to the history of suspected arteritis, chest CT scan was performed in order to rule out the hypothesis of aortic dissection before proceeding to coronarography. No signs of aortic rupture but the presence of thickening of the aorta from the arch to the carrefour was found. The coronary angiography showed critical stenosis in the medial tract of the circumflex artery and thrombotic subocclusion in the middle segment of the right coronary (culprit lesion—Figure 1) that was treated with PCI using drug-eluting stent. The echocardiogram showed mild left ventricular disfunction (EF 53%) due to posterolateral hypokinesia, no other pathological findings. Blood tests revealed anaemia, elevated platelets, and an increase of inflammation markers. Peak Hs-troponin was 18 000 ng/L (n.v. < 0.02 ng/ml). After 2 days we performed elective revascularization of the circumflex artery using a drug-eluting stent. Considering the medical history, we performed temporal artery biopsy and a total body PET scan that showed accumulation of radioactive tracer from the aortic arch to the sub-renal abdominal aorta, with a thickened wall. After that empirical corticosteroid therapy was started and some days later the result of the temporal artery biopsy confirmed the diagnosis of Horton arteritis. The patient was discharged to a rehabilitation structure in good general condition with cardioactive and corticosteroid therapy after 9 days of hospitalization. Conclusions: Horton arteritis usually involves the external carotid artery and its branches, but sometimes inflammation of the aorta occurs in a subgroup of patients and rarely can involve the coronary arteries. An acute coronary syndrome in patients with Horton arteritis can be very insidious because aortic dissection can be the hidden cause, so chest CT scan must be performed before coronary angiography to avoid acute complication associated with an elevated mortality. Furthermore, being the vasculitic inflammation the trigger of the coronary involvement immunosuppressive therapy could be helpful to prevent subsequent acute coronary events.